TREATMENT OUTCOMES OF PEDIATRIC SUPRACONDYLAR HUMERAL FRACTURES USING CLOSED REDUCTION AND PERCUTANEOUS PINNING UNDER FLUOROSCOPIC GUIDANCE (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate outcomes of closed reduction and percutaneous pinning for supracondylar humeral fractures under fluoroscopic guidance.Methods: A combined retrospective and prospective descriptive study on 115 patients treated at Ha Tinh General Hospital (Jan 2024–Dec 2025). Data included demographics, Gartland classification, fixation methods, union time, complications, and functional outcomes assessed by Flynn criteria.Results: Patients aged 6–10 years accounted for 49.6%, males 67.8%. The main cause was fall on outstretched hand (39.1%). Gartland type III was most common (53.0%). Cross pinning was used in 56.5%. Mean operative time was 30 ± 15.9 minutes; mean union time 8 ± 8.5 weeks. Good union achieved in 84.3%, with no nonunion. According to Flynn criteria, good and excellent outcomes reached 88.7%. Complications included elbow stiffness (10.4%) and pin tract infection (4.3%), with no nerve injury recorded.Conclusion: Closed reduction with percutaneous pinning under fluoroscopy is an effective method, providing high union rates, good functional outcomes, and low complication rates.
Keywords: supracondylar humeral fracture; percutaneous pinning; fluoroscopy; Flynn criteria.